PERBEDAAN RERATA KADAR IL-6 SERUM MATERNAL BERDASARKAN KEBERHASILAN PEMBERIAN TOKOLITIK PADA PARTUS PREMATURUS IMMINENS - Joserizal Serudji; Rika Effendy; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2019)
Preterm labor needs to be prevented, one of the prevention methods is by tocolytic administration which could prevent labor thus providing a chance for lung maturation. Preterm Pregnancy is associated with increased concentrations of cytokines such as Interleukin (IL). The increasing concentration of maternal serum IL-6 can be used to predict preterm labor. This research uses the design Cross-Sectional Comparative to determine differences in means of maternal serum levels of IL-6 based on the success of the administration of a tocolytic agent on preterm labor. This study was performed on pregnant women who come to the obstetric emergency room of DR. MA. Hanafiah Batusangkar Hospital within August-November 2015. The total number which was included in statistical analysis was 34 pregnant women which were divided into 2 groups, 17 people in the group of patients who failed in tocolytic agent administration, and 17 people in the group who success in managed with a tocolytic agent. Statistical analysis was performed to analyze the validity using the T-test. There are significant differences in the average rate of maternal serum IL-6 in patients who failed to treat with a tocolytic agent and successful to treat with a tocolytic agent. Seen from the p-value 0.000. Levels of maternal serum IL-6 in patients who failed to treat with a tocolytic agent were higher than successful to treat with a tocolytic agent.Keywords: IL-6, Tocolytic, Preterm labor